Simulation and Modeling Methodologies, Technologies and Applications International Conference, SIMULTECH 2016 Lisbon, Portugal, July 29-31, 2016, Revised Selected Papers (Advances in Intelligent Systems and Computing,, 2018)
This Proceedings book reports on new and innovative solutions regarding methodologies and applications of modeling and simulation. It includes a set of selected, extended papers from the 6th International Conference on Simulation and Modeling Methodologies, Technologies and Applications (SIMULTECH 2016), held in Lisbon, Portugal, from 29 to 31 July, 2016. The conference brought together researchers, engineers and practitioners interested in methodologies and applications of modeling and simulation. SIMULTECH 2016 received 76 submissions from 35 countries and all continents. After a double-blind paper review performed by the Program Committee, 18% were accepted as full papers and thus selected for oral presentations. Additional papers were accepted as short papers and posters. A further selection was made after the Conference, based also on the assessment of presentation quality and audience interest, so that this book includes the extended and revised versions of the very best papers from SIMULTECH 2016. .